Modern challenges in the mental health care system and the role of psychoeducation in overcoming them - Shuliakova Марія (Psychosomatic Medicine and General Practice, 2025)
The article examines the key problems of the modern mental health care system, caused by social transformations, the military context, global crises, and the changing paradigm of psychiatric care. Special attention is paid to psychoeducation as a tool for increasing the stress resistance of the population, reducing the stigmatization of mental disorders, supporting effective rehabilitation and preventing repeated mental episodes. Promising directions for the development of psychoeducational programs in the medical, social and educational spheres are outlined. The purpose of the study is to provide a theoretical, analytical and evidence-based justification of the importance of psychoeducation in the structure of modern care systems, as well as to determine its potential in reducing emotional and social stress, improving adherence to treatment, and preventing relapse of mental disorders. The paper presents a review of international studies confirming the effectiveness of psychoeducational programs for psychotic, bipolar, anxiety, and depressive disorders, and also shows the benefits of family-centered and digital intervention formats. The scientific novelty lies in the actualization of the issue of scaling up psychoeducation in Ukraine, taking into account the socio-psychological consequences of a full-scale war, internal migration, and the shortage of specialized specialists. The practical significance of the results obtained lies in the possibility of using psychoeducational technologies as a component of systemic support for the population, a tool for early intervention and building resilience, as well as in the potential for implementing these programs in medical, educational, and public institutions at the state level. Keywords: psychoeducation, healthcare system, war, stigmatization, depression, anxiety, PTSD